Speed control with and without advanced warning sign on the field: An analysis of the effect on driving speed. (June 2016) - Wilmots, Brenda; Hermans, Elke; Brijs, Tom; Wets, Geert
Highlights: Speed control in an unmarked police car significantly reduces the speed level. Also the combination of it with an advanced warning sign reduces the traveled speed. Generally the effect of the combination is larger. There seems to be a limited time halo effect which is stronger in case of the combination. Abstract: Speeding is an important risk factor in road safety and police activities with regard to traffic (safety) are therefore to a large extent focused on tackling this problem. Within this study, researchers from Hasselt University worked together with 3 regional police units to test the effect of two frequently used speed interventions namely a speed control (i.e. stationary police control in an unmarked police car equipped with a mobile radar) with and without an advanced (digital) warning sign alongside the road. The effect of these 2 types of interventions is tested on two road segments of regional roads (with a maximum speed of 70 and 90 km/h), whereby interventions were switched between both roads during the second field experiment. To measure the effect of both methods, the average speed, 85th percentile of speed and odds of drivers exceeding the speed limit were analyzed, mainly by using general linear regression models. Results show for each tested intervention, significant speed reductions during the time that enforcement was in place. Generalizing these results, allows us to conclude that the effect during the speed control with advanced warning sign is larger compared to the speed control only (respectively −4.5 km/h and −2.5 km/h in the V85 speed) and also the continuing effect until one week after the intervention is higher. In the future, we recommend repeating the experiment on more locations, to enhance the reliability and generalizability of the results. To do so, further cooperation between knowledge institutions and field practitioners is advisable.